Roles for advisory science in the International Council for the Exploration of the Sea (ICES). (February 2023) - Linke, Sebastian; Nielsen, Kåre Nolde; Ramírez-Monsalve, Paulina
Abstract: What role should science take when providing advice in support of policy and politics? Should a provider of science-based advice have its own position on the issues it provides advise on? Or should it be as impartial as possible from the value and policy context of the advice? This theme, long debated, gained new attention in fisheries and marine governance. Starting from theoretical concepts and stylised models, this study attends to a theory-practice gap by investigating concrete advisory practices. We analyse roles that the International Council for the Exploration of the Sea (ICES) takes when producing and delivering science-based advice. ICES is an interesting case because its long history as advice provider offered it unique opportunities to consolidate and refine its advisory role. Published by the Advisory Committee in ICES, the 2021 "Guide to ICES advisory framework and principles" describes the overarching framework to ICES advice and the principles it builds on. Based on this guide, we analyse the forms of science-policy interactions and roles that ICES takes as advisor, how these roles are enabled, and the challenges they involve. We find that ICES takes different roles vis-à-vis policy and society for different contexts in which it provides advice. Our analysis of ICES' advice portfolio provides lessons on how different advice products can be developed through structured processes in a way that helps to bridge the boundary between science and policy and support the enactment of what ICES sees as appropriate advisory roles.